The Training of Porphyry’s ‘Athlete’: The Ascetic Philosopher in On the Abstinence from Eating Flesh - Gamlath, Isha (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2018)
The image of the historical athlete who enters the ancient Greek stadium is a perfect medium for clarifying the conceptual philosopher’s liberation from material bonds and ascent to the higher causal order in Porphyry’s On the Abstinence from Eating Flesh. The image is emphasized when Porphyry prescribes the practice of vegetarianism and immaterial sacrifice for the conceptual philosopher’s preparation for the specific ‘contest’ of freeing from material concerns such as food and sacrifice and eventual transformation in to the as the priest of the Highest God.